2022
DOI: 10.1111/jan.15367
|View full text |Cite
|
Sign up to set email alerts
|

Is the Australian nursing workforce ready to embrace prescribing under supervision? A cross‐sectional survey

Abstract: Aim:The aim was to explore nurses' preparedness to expand their practice to prescribe medicines under a supervision model. Design:This was a cross-sectional study. Methods: A convenience sample of Australian nurses recruited from memberships of State-based Nursing and Midwifery Unions and professional bodies from diverse care settings. Nurses undertook an online researcher-constructed survey between March and July 2021 to identify current prescribing practices, motivations for undertaking education in prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Most participants agreed that the implementation of nurse prescribing under supervision would improve the outcomes of patients, clinicians, and organizations in Saudi Arabia. Comparable findings from other countries have shown that expanding prescribing practices to nurses would increase the benefits of and access to healthcare services and medicine ( Armstrong, 2015 , Casey et al, 2020 , Fox et al, 2022 , Gielen et al, 2014 , Nuttall, 2018 ), provide patient-centered care to maintain the continuity of care ( Armstrong, 2015 , Casey et al, 2020 , Fox et al, 2022 , Nuttall, 2018 ), improve nurse experiences and satisfaction ( Armstrong, 2015 , Casey et al, 2020 , Cousins and Donnell, 2012 , Fox et al, 2022 , Gielen et al, 2014 , Lennon and Fallon, 2018 ), and enhance the safety and effectiveness of clinical practices and optimal care ( Armstrong, 2015 , Azami et al, 2018 , Tinelli et al, 2015 , Wilson et al, 2021 ). Although previous studies identified several professional advancements for nurses as outcomes for prescribing practices ( Fox et al, 2022 , McBrien, 2015 , Romero-Collado et al, 2014 ), this study did not explore the potential professional advancements that are expected when granting nurses prescribing authority.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Most participants agreed that the implementation of nurse prescribing under supervision would improve the outcomes of patients, clinicians, and organizations in Saudi Arabia. Comparable findings from other countries have shown that expanding prescribing practices to nurses would increase the benefits of and access to healthcare services and medicine ( Armstrong, 2015 , Casey et al, 2020 , Fox et al, 2022 , Gielen et al, 2014 , Nuttall, 2018 ), provide patient-centered care to maintain the continuity of care ( Armstrong, 2015 , Casey et al, 2020 , Fox et al, 2022 , Nuttall, 2018 ), improve nurse experiences and satisfaction ( Armstrong, 2015 , Casey et al, 2020 , Cousins and Donnell, 2012 , Fox et al, 2022 , Gielen et al, 2014 , Lennon and Fallon, 2018 ), and enhance the safety and effectiveness of clinical practices and optimal care ( Armstrong, 2015 , Azami et al, 2018 , Tinelli et al, 2015 , Wilson et al, 2021 ). Although previous studies identified several professional advancements for nurses as outcomes for prescribing practices ( Fox et al, 2022 , McBrien, 2015 , Romero-Collado et al, 2014 ), this study did not explore the potential professional advancements that are expected when granting nurses prescribing authority.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the rated facilitating factors for nurse prescribing reported in this study were consistent with those reported in previous studies. For instance, organizational and collegial factors that influenced nurse prescribing include support from their organization as well as nurses and non-nursing colleagues ( Bowskill et al, 2013 , Brimblecombe and Dobel-Ober, 2022 , Fox et al, 2022 , Smith et al, 2014 , Snell et al, 2022 , Stenner et al, 2010 ), having a mentor and continuing professional training ( Carey and Courtenay, 2008 , Carey et al, 2010 , Courtenay and Carey, 2008 , Snell et al, 2022 , Stenner et al, 2010 ), unrestricted scope of practice ( Lockwood and Fealy, 2008 , Muyambi et al, 2018 , Stenner et al, 2010 ), and financial reward for prescribing practice ( Maddox et al, 2016 ). Other factors include acceptance and support from patients ( McCann and Clark, 2008 ) and perceived confidence and competency ( Carey et al, 2014 , Maddox et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations